Bulk and surface plasmons in highly nanoporous gold films - Maaroof, Abbas I. (Animo Repository, 2007)
The far field plasmonic behaviour of nanoporous gold films with void densities ranging from 60% to 90% has been investigated and modelled. These layers have good dc conductivity and quite different nanostructure to traditional porous layers in which the metal percolates. Our gold films with void density f above 70% have high thermal emittance for a conductor at their thicknesses and their flat spectral response at visible and near infrared wavelengths is not metal like. We derive effective optical constants which become plasmonic at wavelengths between 1.8 and 4 µm for f from 72 to 87%. This onset is much longer than that in bulk gold. For void densities below 70% the onset of plasmonic behaviour is much closer to the dense material. A simple test is implemented to test for surface plasmon polaritons (SPPs) under illumination. The more porous films show no evidence of SPP, while the less porous films display weak evidence. Thus by tailoring void content in these nanostructures we can tailor the onset of effective plasmonic response across a wide range from 0.8 to 4 µm and emittance from around 0.9 down to low values. An effective uniform metal response is thus found in the presence of surface nanostructure without the interface absorption found in dense gold layers with structured surfaces.